MOTIVASI INDONESIA BERKERJASAMA DENGAN TURKI DALAM MENINGKATKAN EKSPOR CRUDE PALM OIL (CPO) (2010-2014) - ", Pujiyono; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research discusses economic cooperation done Indonesia with Turkey to improve the volume of exports crude palm oil/CPO to Turkey. especially from the signing of the Memorandum of Understanding between the Government of the Republic of Indonesia and the Government of the Republic of Turkey on Agricultural.The method used in this research is qualitative research. Some of the data obtained came from books, journals, articles, annual reports, the internet and other media. In this study also used the perspective of liberalism, international cooperation theory, and national interest Concept. Scope of this research is motivation indonesia in cooperation with turkey in an effort to increase their exports crude palm oil cpo ( ) indonesia to turkeyThis research showed that indonesia and turkey has good relations in all things especially in the trade sector. Turkey has an important role for trading partners indonesia , remember position turkey which is very strategic. The purpose of indonesia in cooperation with turkey is to promote the product of palm indonesia to Turkey , as well as making turkey as a way to open up the opportunity to export markets to other countries in about turkey or the Balkan countries and Europe..Key words: National Interests, CPO exports, MoU, Turkey as indonesia strategic trading partner.